2021
DOI: 10.1177/01461672211037138
|View full text |Cite
|
Sign up to set email alerts
|

Psychology and the Threat of Contagion: Feeling Vulnerable to a Disease Moderates the Link Between Xenophobic Thoughts and Support for Ingroup-Protective Actions

Abstract: The widespread threat of contagious disease disrupts not only everyday life but also psychological experience. Building on findings regarding xenophobic responses to contagious diseases, this research investigates how perceived vulnerability to a disease moderates the psychological link between people’s xenophobic thoughts and support for ingroup-protective actions. Three datasets collected during the time of Ebola ( N = 867) and COVID-19 ( Ns = 992 and 926) measured perceived disease risk, group-serving biase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In the present study, we investigated the role of the cultural dimension of collectivism, controlling for individualism. Individualistic and collectivistic value orientations have been shown to have distinct effects on behavioral outcomes [ 11 ], and prior work has shown that collectivistic-values orientation is a stronger predictor of responses to collective threats such as climate change [ 15 ] and contagious diseases [ 12 , 16 ] than individualistic-values orientation. For example, in the face of Ebola, for people who were at high levels of perceived disease vulnerability, collectivism was associated with reduced xenophobic policy support, possibly because they perceived greater protection from their community against pathogen threat, whereas individualism was not associated with xenophobic policy support [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we investigated the role of the cultural dimension of collectivism, controlling for individualism. Individualistic and collectivistic value orientations have been shown to have distinct effects on behavioral outcomes [ 11 ], and prior work has shown that collectivistic-values orientation is a stronger predictor of responses to collective threats such as climate change [ 15 ] and contagious diseases [ 12 , 16 ] than individualistic-values orientation. For example, in the face of Ebola, for people who were at high levels of perceived disease vulnerability, collectivism was associated with reduced xenophobic policy support, possibly because they perceived greater protection from their community against pathogen threat, whereas individualism was not associated with xenophobic policy support [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, collectivistic values orientation (but not individualistic values orientation) interacted with beliefs about climate change to predict climate action [ 15 ]. Not only is collectivistic values orientation a stronger predictor of response to collective threats, but people respond to collective threats by endorsing collectivistic values [ 7 , 16 ]. In an examination of the difference in endorsement of collectivistic and individualistic values before and after the announcement of COVID-19 outbreak in South Korea, Na and colleagues found that individuals endorsed stronger collectivistic values, but there were no significant changes in the endorsement for individualistic values [ 13 ].…”
Section: Introductionmentioning
confidence: 99%